THE EFFECT OF COMPETENCE, LEADERSHIP, AND MANAGEMENT INNOVATION OVER THE PERFORMANCE OF STRUCTURAL OFFICIAL OF ECHELON IVB - Bedjo Sujanto; Maruf Akbar; Darmawan Apriyadi (IJHCM (International Journal of Human Capital Management), 2017)
Abstract The aim of this research was to analyze the effect of competency, leadership, and innovations management on structural office holder of echelon IVB performance.This research was conducted at the One Stop Service Agency of Province of DKI Jakarta, using the method of path analysis in hypothesis testing. The sample in this research is of 75 people with simple random sampling. The results of this study are: (1) Competency positive direct effect on structural office holder echelon IVB performance. (2) Leadership positive direct effect on structural office holder echelon IVB performance. (3) Management of Innovation positive direct effect on structural office holder echelon IVB performance. (4) Competency positive direct effect on Management of Innovation, and (5) Leadership positive direct effect on Management of Innovation.The results of this research has implications for the effect of competency, leadership, and innovations management which can support on the structural office holder of echelon IVB performance One Stop Service Agency of Province of Jakarta Special Capital Region. Keywords: Performance, Competency, Leadership, Innovation Management